2018
DOI: 10.1080/10942912.2018.1451343
|View full text |Cite
|
Sign up to set email alerts
|

Texture characteristics of chilled prepared Mandarin fish (Siniperca chuatsi) during storage

Abstract: Mandarin fish that have been prepared and chilled have a shelf life of 4 days at 4°C storage, according to the total volatile basic nitrogen values. During the storage process, we observed that the texture characteristics of these fish significantly deteriorated. Certain low-abundance proteins were degraded during the shelf life, which resulted in changes in protein conformation and protein-water interaction patterns. The water-holding capacity of the fish decreased during 4°C storage; nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
1
28
1
Order By: Relevance
“…However, our previous study proved that there is no obvious degradation of myosin and actin in mandarin fish over the shelf life period (Sun et al , ), which is inconsistent with the results of other researches (Ramirez‐Suarez et al , ; Yang et al , ). Some published reports indicated that the quality characteristics of fish muscle might be influenced by structural proteins, regardless of myosin and actin (Ahmed et al , ; Singh & Benjakul, ).…”
Section: Introductioncontrasting
confidence: 68%
See 3 more Smart Citations
“…However, our previous study proved that there is no obvious degradation of myosin and actin in mandarin fish over the shelf life period (Sun et al , ), which is inconsistent with the results of other researches (Ramirez‐Suarez et al , ; Yang et al , ). Some published reports indicated that the quality characteristics of fish muscle might be influenced by structural proteins, regardless of myosin and actin (Ahmed et al , ; Singh & Benjakul, ).…”
Section: Introductioncontrasting
confidence: 68%
“…After being washed with tap water, the fish were stored at 4 °C for 3 h, and the dorsal muscle was cut into blocks (approximately 30 × 20 × 10 mm). Then, the fish blocks were packed in a crisper at 4 °C and sampled at different post‐mortem times (1–5 days) according to Sun et al (). After being steamed for 5 min, the cooked fish blocks were obtained for a comparative study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2.4 N, but considerably lower than those found by Sáez et al [ 44 ] also for meagre fillets, ca. 30 N. Besides inter-specific differences in morphology and the interaction between myofibrillar proteins and water during storage [ 47 ], numerous factors affect texture measurements in fish and fish products [ 48 ]. Differences in equipment and procedures, as well as the size of fillets could have influenced the texture determinations.…”
Section: Resultsmentioning
confidence: 99%